Adoption and use of an injury prevention exercise programme in female football: a qualitative study among coaches - Lindblom, H.; Carlfjord, S.; Hägglund, M. (Scandinavian Journal of Medicine & Science in Sports, 2018)
This study focuses on an injury prevention exercise program (IPEP), Knee Control, which has been shown to reduce the incidence of acute knee injury in female adolescent football players. The aim was to explore the factors influencing coaches` adoption and use of Knee Control within female football in Sweden. This was a qualitative study involving interviews with 20 strategically selected coaches for female football teams, predominantly adolescent teams. The semi-structured interview guide was influenced by the Health Belief Model, and an ecological perspective was adopted during the interviews. Interviews were analyzed with qualitative content analysis. The results illustrate the different influences that interact on adoption and use of Knee Control by coaches. The coaches described themselves as crucial for Knee Control adoption and use, but external facilitators and barriers such as resources for training, social support from other coaches, clubs and football associations and player buy-in were also described as important. Knee Control characteristics, such as how well the program fit the team, also influenced use of Knee Control. Many coaches modified the program to improve player buy-in and Knee Control fit. Such modifications may risk compromising the preventive effect but may increase feasibility, that is the ease of using Knee Control, and thereby long-term use. These findings may guide the design and delivery of future IPEPs, and improve use of Knee Control, for example, by expanding the program to fit different target groups and supporting coaches and players in the use of Knee Control.